SAT0083 PREVALENCE OF FRAILTY AND ITS ASSOCIATED FACTORS IN PATIENTS WITH RHEUMATOID ARTHRITIS: A CROSS-SECTIONAL ANALYSIS. (June 2019) - Carlo, Marco DI; Farah, Sonia; Donato, Eleonora DI; Carotti, Marina; Salaffi, Fausto
Abstract : Background: The concept of frailty is a recent issue in the rheumatologic field, by now, the prevalence of frailty among individuals with rheumatoid arthritis (RA) has not been extensively examined and few studies on frailty in RA adults have been conducted. Moreover, the relationship between frailty and sociodemographic or disease characteristics in RA are unknown. Objectives: The aims of the present research were to assess the prevalence of frailty and its potential associated factors in adult patients with RA. Methods: Consecutive RA patients and healthy controls were assessed according the Survey of Health, Ageing and Retirement in Europe Frailty Instrument (SHARE-FI) (1), and classified as frail, pre-frail or non-frail. Patients underwent to a clinimetric assessment in order to establish disease activity (Simple Disease Activity Index [SDAI]), function (Health Assessment Questionnaires Disability Index [HAQ-DI]), comorbidities (modified Rheumatic Disease Comorbidity Index [mRDCI])(2), and radiographic damage (Simple Erosion Narrowing Score [SENS]). Chi-square, analysis of variance (ANOVA), and multinomial logistic regression analyses were used to test the prognostic value of frailty for the outcomes of interest. Results: 210 consecutive RA patients were included (72 male, 138 female) and the mean age was 60.4 years. The study group was composed by 100 healthy controls (63 females and 47 males). The mean age was 59.1. According to SHARE-FI criteria, 35 RA patients (16.6%) were categorized as frail, 68 (32.4%) as pre-frail, and 107 (51%) as non-frail, while 8 control subjects were categorized as frail, (8%), 17 as pre-frail (17%), and 75 as non-frail (75%) (chi-squared 12.8; p=0.0016). The results from logistic regression analysis revealed that age (odd ratio [OR] = 1.12, 95% confidence interval [CI] = 1.07-1.17; P <0.0001), comorbidities (OR = 1.51, 95% CI = 1.01-2.27; P = 0.0446), and high disease activity (OR = 1.10, 95% CI = 1.04-1.16; P = 0.0006) were independently associated with frailty in RA patients (Fig 1 ). Conclusion: Frailty or pre-frailty are common in RA. The SHARE-FI may be a specific tool for the screening of frailty in RA and may summarize the results of a comprehensive RA assessment providing a marker of deficits accumulation. Future studies will need to examine longitudinal relationships between frailty and health outcomes in RA. References: [1] Romero-Ortuno R, Walsh CD, Lawlor BA, et al. A frailty instrument for primary care: findings from the Survey of Health, Ageing and Retirement in Europe (SHARE). BMC Geriatr2010;10:57 [2] Iannone F, Salaffi F, Fornaro M, Di Carlo M, Gentileschi S, Cantarini L, Lopalco G. Influence of baseline modified Rheumatic Disease Comorbidity Index (mRDCI) on drug survival and effectiveness of biological treatment in patients affected with Rheumatoid arthritis, Spondyloarthritis and Psoriatic arthritis in real-world settings. Eur J Clin Invest. 2018;48(11):e13013. Disclosure of Interests: Marco Di Carlo: None declared, sonia farah: None declared, eleonora Di Donato: None declared, marina carotti Speakers bureau: abbvie pfizer novartis roche bms sanofi, Fausto Salaffi Grant/research support from: Abbvie, Roche, Novartis, BMS, Pfizer, Sanofi, Speakers bureau: Abbvie, Roche, Novartis, Pfizer, Sanofi, BMS